Effect of System Parameters on Natural Frequency of the Pelton Turbine - Motra, Laxman; Karki, Sanjeev (Journal of Advanced College of Engineering and Management, 2018)
The effect of diameter, length and rotational speed of shaft, and mass of runner-buckets assembly on the natural frequency of the Pelton turbine unit was analyzed. Effect of the decisive parameters on the natural frequency of the unit showed that it was directly proportional to the diameter of the shaft and inversely proportional to the length of the shaft and mass of the runner-buckets assembly. For the continuous system model, when the rotational speed of the shaft increased, the natural frequency for the forward whirl also increased but the natural frequency decreased for the backward whirl.